Innate stimulatory capacity of high molecular weight transition metals Au (gold) and Hg (mercury). Issue 2 (March 2015) - Rachmawati, Dessy; Alsalem, Inás W.A.; Bontkes, Hetty J.; Verstege, Marleen I.; Gibbs, Sue; von Blomberg, B.M.E.; Scheper, Rik J.; van Hoogstraten, Ingrid M.W.
Highlights High molecular weight transitional metals Au and Hg activate innate immunity. Gold and mercury induce IL-8 secretion in myelo-monocytic cells. Stimulatory capacity of Au could be ascribed to TLR-3 ligation. Innate responses may contribute to development of oral and skin allergies.